Pareto stable matchings : an empirical study - Le, Truc Viet (2013)
One of the important functions of many markets and social processes is to match one kind of agent with another. Well-known examples include students and colleges, workers and firms, marriageable men and women, and so on. When the set of agents can be partitioned into two disjoint subsets, each desires to be matched with another, we have a two-sided matching market. Thus, a matching is the outcome of the interactions between agents on both sides of the market and the process that produces such a matching is called a matching mechanism. Due to its versatile ability to model many essential social and economic activities, two-sided matching markets have been well studied in the economics and game theory literature.